Legal Realism and the Future of Palm Oil Management in Indonesia - Sayuti, Ageng Triganda; Windarto, Windarto; Martadinata, Muhammad Randhy; Ridho, Muhammad Ali; Kadir, Sulhi Muhamad Daud Abdul (Jambe Law Journal, 2025)
Through the jurisprudential lens of Roscoe Pound, particularly his doctrines of legal realism and sociological jurisprudence, this article explores palm oil plantation management contracts. By situating contract law within the broader framework of social engineering, the study critiques the prevailing contractual practices in Indonesia's palm oil sector, which often privilege corporate profit at the expense of local communities and environmental sustainability. The analysis reveals a persistent asymmetry in power and legal capacity between plantation companies and rural populations, resulting in contracts that fail to deliver substantive justice. Drawing from Pound’s tripartite interest theory, individual, social, and public, the study argues that current contractual frameworks inadequately integrate ethical, ecological, and communal considerations. This research offers a normative proposal to redesign plantation management contracts as instruments of equitable governance. It advocates for a participatory and inclusive legal drafting process that recognizes local wisdom, ensures environmental accountability, and promotes distributive justice. By embedding Roscoe Pound’s vision of law as a dynamic, purposive institution, the article contributes to the evolving discourse on legal reform in natural resource management. Ultimately, it calls for a reconceptualization of contracts not merely as tools of economic transaction but as living legal instruments capable of reconciling corporate interests with the imperatives of social justice and environmental stewardship